Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/v14061141
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Effect of Antibodies against the SARS-CoV-2 Nucleoprotein

Abstract: COVID-19 caused by SARS-CoV-2 is continuing to spread around the world and drastically affect our daily life. New strains appear, and the severity of the course of the disease itself seems to be decreasing, but even people who have been ill on an outpatient basis suffer post-COVID consequences. Partly, it is associated with the autoimmune reactions, so debates about the development of new vaccines and the need for vaccination/revaccination continue. In this study we performed an analysis of the antibody respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The 2022 study by Matyushkin D. et al identified alleles linked to heightened susceptibility to autoimmune processes post-COVID-19, notably HLA A01:01, A26:01, B39:01 and B15:01 alleles [48], which were also found in our patient. These findings suggest a potential association between the detected alleles in the case under discussion and systemic diseases that lead to uveitis, alongside a correlation with autoimmune complications following COVID-19 infection.…”
Section: Discussionsupporting
confidence: 70%
“…The 2022 study by Matyushkin D. et al identified alleles linked to heightened susceptibility to autoimmune processes post-COVID-19, notably HLA A01:01, A26:01, B39:01 and B15:01 alleles [48], which were also found in our patient. These findings suggest a potential association between the detected alleles in the case under discussion and systemic diseases that lead to uveitis, alongside a correlation with autoimmune complications following COVID-19 infection.…”
Section: Discussionsupporting
confidence: 70%
“…In addition to natural infection, the production of N-specific antibodies can be stimulated by immunization with whole-virion inactivated [ 22 , 23 ] or live attenuated [ 24 ] vaccines; however, the mechanism of involvement of these immunoglobulins in protection against COVID-19 remains largely unstudied. Moreover, there is evidence that anti-N antibodies may have autoimmune properties, provoking the development of various immunopathological conditions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV and SARS-CoV-2 coronaviruses have been shown to cause the production of autoantibodies; in particular, in SARS-CoV-2, the antibodies to major viral antigens (S- and N-proteins) are cross-reactive to human proteins [ 139 ]. In animals, after immunization with a vaccine derived from inactivated and purified SARS-CoV virus, antibodies targeted to normal cell components, including the carbohydrate chains of human orosomucoid, were detected [ 117 ].…”
Section: Anti-glycan Antibodies As Ade Triggermentioning
confidence: 99%